Dark chocolate administration improves working memory in students - Prastowo, Nawanto Agung; Kristanto, Samuel; Sasmita, Poppy Kristina (Universa Medicina, 2015)
BackgroundFlavonoids have positive effects on health, including the nervous system. High flavonoid content can be found in chocolate, especially dark chocolate. Verbal working memory is important for reasoning, language comprehension, planning, and spatial processing. The purpose of this study was to evaluate the effect of a single dose of dark and white chocolate administration on verbal working memory in medical students. MethodsA study of experimental pre-post test design with controls was conducted on 60 students. These were simply randomized into two groups: the first group was supplemented with white chocolate as control, and the second group received dark chocolate, at an identical single dose of 100 g. Working memory was measured with the digit span forwards (DSF) and the digit span backwards (DSB) tests, before, at 1 hour, and at 3 hours after intervention. Independent t and Mann-Whitney tests were used for data analysis. ResultsScores for DSF and DSB in control and treatment groups were similar at baseline. At 1 hour after dark and white chocolate administration, DSF and DSB scores were not significantly different between the two groups (p=0.832; p=0.683). Supplementation of dark chocolate at 3 hours after intervention significantly increased DSB scores compared to white chocolate (p=0.041), but DSF scores were not significantly different between the two groups (p=0.204). ConclusionsDark chocolate as a single dose is capable of improving verbal working memory in students, 3 hours after its consumption. Since cocoa contains multiple bioactive compounds, one approach might be to examine the neurocognitive effects of combinations of potential functional ingredients.